Model Pembelajaran Dick and Carrey dalam Pembelajaran Bahasa dan Sastra Indonesia di SDN Pondok Jagung Timur Kota Tanggerang Selatan - Magdalena, Ina; Aen, Kurotul; Maulidya, Sarah; Fadilah, Nur (TSAQOFAH, 2023)
The purpose of this research is to investigate how elementary school students use the Dick and Carrey model to learn literature and language. There are a variety of learning design development models, each with its own benefits and drawbacks. The Dick and Carroll model is thought to be able to address Indonesian language learning issues. The literature review was the method used in this study. According to the study's findings, learning design development models will be able to adapt to changing times that necessitate increasingly inventive model development designs. It is fascinating to investigate each learning design development model in light of the growing number of them. There are certain distinguishing features that each learning design development model shares that contribute to its individuality. Additionally, this model is in line with elementary school students' interests in play, which makes learning more enjoyable and encourages students to follow it.